Analysis of Prevalence and Contributing Factors for Advanced HIV Disease at Wangaya Denpasar General Hospital: January 2022 to December 2023 - Anak Agung Ayu Mita Astari; Ketut Suryana (Bali Medical and Wellness Journal, 2024)
Background: Advanced HIV disease (AHD) remains a significant health concern and a leading cause of mortality among individuals living with HIV/AIDS. Understanding the psychosocial factors influencing AHD, such as social support, access to healthcare resources, and mental health conditions like depression, is vital for effective intervention. Aim: This study aimed to determine the prevalence of AHD and identify the factors associated with it at Wangaya Denpasar General Hospital from January 2022 to December 2023. Methods: A cross-sectional study was conducted involving all newly diagnosed AHD patients at the Merpati clinic, Wangaya General Hospital, during the specified period. Participants were selected based on inclusion and exclusion criteria, and data were collected through a comprehensive review of patients' medical records. Results: Out of 128 newly diagnosed individuals living with HIV/AIDS (PLWHA), 84 (65.6%) were classified as having AHD. The majority of PLWHA with AHD were male (73.8%), under 50 years of age (82.1%), without a college education (94.0%), unemployed (83.3%), married (54.8%), had medical insurance (90.5%), contracted HIV through heterosexual contact (90.5%), were referred from other medical facilities (82.1%), and reported having social support (98.8%). Significant factors associated with AHD included lack of college education (p=0.000), unemployment (p=0.000), marital status (p=0.037), and referral source (p=0.010). Conclusion: The findings indicate that lack of college education, unemployment, marital status, and being referred from other medical facilities are significant factors associated with AHD. To mitigate AHD-related morbidity and mortality, it is essential to enhance education and training programs focused on HIV/AIDS and to promote provider-initiated HIV testing and counseling. This approach could facilitate earlier prevention and diagnosis of HIV.